1997
DOI: 10.1093/carcin/18.10.1883
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and mammalian DNA alkyltransferases sensitize Escherichia coli to the lethal and mutagenic effects of dibromoalkanes

Abstract: Here we confirm and extend our previous studies demonstrating that the mutagenic potency of 1,2-dibromoethane (DBE) and dibromomethane (DBM) is markedly enhanced (not prevented) in bacteria expressing the O6-alkylguanine-DNA alkyltransferase (ATase) encoded by the Escherichia coli ogt gene. We demonstrate that, in close parallel with mutagenesis, the Ogt ATase sensitizes the bacteria to the lethal effects of these carcinogens, suggesting that one or more of the potentially mutagenic lesions induced by DBE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…As shown in Fig. 1, BE is neither cytotoxic nor mutagenic in TRG8 cells irrespective of their AGT status, suggesting that the observed DBE toxicity in E. coli expressing high levels of Ogt, Ada, or hAGT (7,8,10,12) and Chinese hamster lung fibroblasts expressing Ogt (12) results from unmetabolized DBE rather than from BE. The difference of DBE and BE in inducing toxicity in AGT-expressing cells indicates that having two good leaving groups is critical for bringing about this toxicity.…”
mentioning
confidence: 90%
“…As shown in Fig. 1, BE is neither cytotoxic nor mutagenic in TRG8 cells irrespective of their AGT status, suggesting that the observed DBE toxicity in E. coli expressing high levels of Ogt, Ada, or hAGT (7,8,10,12) and Chinese hamster lung fibroblasts expressing Ogt (12) results from unmetabolized DBE rather than from BE. The difference of DBE and BE in inducing toxicity in AGT-expressing cells indicates that having two good leaving groups is critical for bringing about this toxicity.…”
mentioning
confidence: 90%
“…During the 1990s, a number of papers appeared demonstrating that expression of the DNA repair protein AGT 1 increased the toxicity and mutagenicity of Br(CH 2 ) 2 -Br in bacterial systems (38)(39)(40)(41). These findings were unexpected, but results with hAGT and Br(CH 2 ) 2 Br now demonstrate that the mechanism involves attack of the highly nucleophilic Cys 145 (42) of (h)AGT on Br(CH 2 ) 2 Br to generate AGT-Cys 145 -S(CH 2 ) 2 Br, which appears to undergo similar reactions to GS(CH 2 ) 2 Br (12) and react with DNA, leading to cross-linking (43).…”
Section: Introductionmentioning
confidence: 99%
“…AGT is inactivated by the alkyl group transfer, and therefore additional repair requires new protein synthesis. Although an early study reported that the mutagenicity of 1,2-dibromoethane (DBE) was not affected by enzymes that repair alkylation lesions (4), there is now convincing data that AGT paradoxically promotes the toxicity of DBE (5,6). Overexpression of human AGT (hAGT) or AGTs from other species enhances the mutagenicity and lethality of DBE in Escherichia coli (5)(6)(7)(8)(9) and induces growth retardation in mammalian cells (10).…”
mentioning
confidence: 99%